Time is money: general practitioners' reflections on the fee-for-service system - Kristian B. Kraft; Eivor H. Hoff; Magne Nylenna; Cathrine F. Moe; Arnstein Mykletun; Kristian Østby (BMC, 2024)
Abstract Background Fee-for-service is a common payment model for remunerating general practitioners (GPs) in OECD countries. In Norway, GPs earn two-thirds of their income through fee-for-service, which is determined by the number of consultations and procedures they register as fees. In general, fee-for-service incentivises many and short consultations and is associated with high service provision. GPs act as gatekeepers for various treatments and interventions, such as addictive drugs, antibiotics, referrals, and sickness certification. This study aims to explore GPs' reflections on and perceptions of the fee-for-service system, with a specific focus on its potential impact on gatekeeping decisions. Methods We conducted six focus group interviews with 33 GPs in 2022 in Norway. We analysed the data using thematic analysis. Results We identified three main themes related to GPs' reflections and perceptions of the fee-for-service system. First, the participants were aware of the profitability of different fees and described potential strategies to increase their income, such as having shorter consultations or performing routine procedures on all patients. Second, the participants acknowledged that the fees might influence GP behaviour. Two perspectives on the fees were present in the discussions: fees as incentives and fees as compensation. The participants reported that financial incentives were not directly decisive in gatekeeping decisions, but that rejecting requests required substantially more time compared to granting them. Consequently, time constraints may contribute to GPs' decisions to grant patient requests even when the requests are deemed unreasonable. Last, the participants reported challenges with remembering and interpreting fees, especially complex fees. Conclusions GPs are aware of the profitability within the fee-for-service system, believe that fee-for-service may influence their decision-making, and face challenges with remembering and interpreting certain fees. Furthermore, the fee-for-service system can potentially affect GPs' gatekeeping decisions by incentivising shorter consultations, which may result in increased consultations with inadequate time to reject unnecessary treatments.